2015
DOI: 10.1177/0301006615596898
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Perceived Height, Masculinity, and Age on Each Other and on Perceptions of Dominance in Male Faces

Abstract: Several studies have examined the individual effects of facial cues to height, masculinity, and age on interpersonal interactions and partner preferences. We know much less about the influence of these traits on each other. We therefore examined how facial cues to height, masculinity, and age influence perceptions of each other and found significant overlap. This suggests that studies investigating the effects of one of these traits in isolation may need to account for the influence of the other two traits. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 58 publications
5
23
0
Order By: Relevance
“…The male adiposity prototypes were generated by separately averaging male faces with a low BMI ( M  = 22.19 kg/m 2 , SD = 2.52; M age  = 25.10 years, SD = 3.96) and male faces with a high BMI ( M  = 26.47 kg/m 2 , SD = 3.27; M age  = 24.80 years, SD = 3.77). The female adiposity prototypes were generated by separately averaging female faces with a low BMI ( M  = 17.85 kg/m 2 , SD = 0.80; M age  = 22.70 years, SD = 3.56) and females faces with a high BMI ( M  = 24.06 kg/m 2 , SD = 6.34; M age  = 23.40 years, SD = 4.50) (for details see Batres et al 2015). The prototypes were then used to create transforms of the 10 composite faces with ±50% of the shape difference while holding texture and color constant.…”
Section: Methods: Studymentioning
confidence: 99%
“…The male adiposity prototypes were generated by separately averaging male faces with a low BMI ( M  = 22.19 kg/m 2 , SD = 2.52; M age  = 25.10 years, SD = 3.96) and male faces with a high BMI ( M  = 26.47 kg/m 2 , SD = 3.27; M age  = 24.80 years, SD = 3.77). The female adiposity prototypes were generated by separately averaging female faces with a low BMI ( M  = 17.85 kg/m 2 , SD = 0.80; M age  = 22.70 years, SD = 3.56) and females faces with a high BMI ( M  = 24.06 kg/m 2 , SD = 6.34; M age  = 23.40 years, SD = 4.50) (for details see Batres et al 2015). The prototypes were then used to create transforms of the 10 composite faces with ±50% of the shape difference while holding texture and color constant.…”
Section: Methods: Studymentioning
confidence: 99%
“…Ten composite images (five male and five female) were created (each averaging three original faces together) and masked to occlude clothes with a black oval around the head (for details see Batres et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Since male masculinity is associated with dominance (Dijkstra & Buunk, 2001;Batres, Re, & Perrett, 2015), it could be advantageous for women to choose a more masculine male in environments with a high level of male-male competition (Puts, 2010;Brooks et al, 2011). Ryder et al, (2016) found that at the individual level, women preferred more physically formidable and dominant partners when they felt more at risk of crime in public places.…”
Section: Accepted Manuscriptmentioning
confidence: 99%